Optimizing Multimodal Freight Transport : Railway–Airport Integration for Sustainable Logistics in Indonesia - Anisa Mahadita Candrarahayu; Efendhi Prih Raharjo; Hana Wardani Puruhita; I Kadek Surya Putra Adidana (Indonesia Civil Pilot Academy Banyuwagi, 2026)
This study examined the integration of railway infrastructure with airport logistics in Indonesia to improve freight transport efficiency. The objectives were to analyze existing conditions, identify infrastructure and operational needs, assess potential demand for modal shift, and develop an integrated logistics model. A mixed-method approach was used, including cost and time analysis, gravity model, and Analytical Hierarchy Process supported by stakeholder interviews. The results showed that freight transport is still dominated by road, causing high costs, congestion, and environmental impacts. Railway integration can reduce logistics costs by 23.24% and delivery time by 44.6%, with high-potential corridors identified in major regions. Cost, time, and reliability were found to be the main decision factors. The Airport Rail Freight Integrated Hub model is proposed as a phased solution to support efficient and sustainable logistics integration, while also enhancing capacity utilization and strengthening service reliability within the national logistics system.